PERAN KADER POSYANDU DALAM PENDAMPINGAN IBU HAMIL RESIKO TINGGI TERHADAP PEMERIKSAAN KEHAMILAN SELAMA PANDEMI COVID-19 - Eny Susanti (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2020)
Antenatal care to pregnant women at risk is something that must be done at least 4 times during pregnancy to prevent harm to the mother and fetus during birth. The result of preliminary studies in october 2015, in Polindes Pajeruan there are 25 (21%0 of pregnant women experience high risk and in westwern Batuporo polindes 2 there were 19 (15%) of pregnant women experiencing high risk.. In this study, using analytical methods and cross sectional design ". The study population was all pregnant women with high risk as many as 46 people and sample collection by simple random sampling to obtain a sample of 41 people. Collecting data using secondary data, ie a questionnaire about the role of cadres and KIA books about pregnancy testing. The data is processed, served with the cross tabulation then analyzed by Spearman rank test. The results of the study the role of Posyandu cadres are good that most of the 30 people (73%). Antenatal care is largely complete that 34 people (82%). Statistical test results and inspection role of Posyandu cadre of pregnancy in pregnant women with high risk α: 0.05 > ρ: 0,048 means that there is influence between the role of Posyandu cadre with antenatal care in pregnant women with high risk. Suggestions in this study is expected to posyandu cadres in the village is always avtive for help health workers to detect danger signs in pregnancy and antenatal care to accompany him on a regular basis.